2008
DOI: 10.1111/j.1745-7254.2008.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases of the RhoBTB subfamily and tumorigenesis

Abstract: RhoBTB proteins constitute a subfamily of atypical members within the Rho fa mily of small guanosine triphosphatases (GTPases). Their most salient feature is their domain architecture: a GTPase domain (in most cases, nonfunctional) is followed by a prolinerich region, a tandem of 2 broadcomplex, tramtrack, bric à brac (BTB) domains, and a conserved Cterminal region. In humans, the RhoBTB subfamily consists of 3 isoforms: RhoBTB1, RhoBTB2, and RhoBTB3. Orthologs are present in several other eukaryotes, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 62 publications
0
78
0
1
Order By: Relevance
“…Recent studies have suggested that RhoB is involved in tumor suppression. These studies suggested that RhoB was detected in normal tissue yet its expression was dramatically lost during cancer progression in lung and head and neck squamous cell carcinoma [37], [38]. In line with these findings, high expression of RhoB was associated with favorable outcome in bladder cancer.…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have suggested that RhoB is involved in tumor suppression. These studies suggested that RhoB was detected in normal tissue yet its expression was dramatically lost during cancer progression in lung and head and neck squamous cell carcinoma [37], [38]. In line with these findings, high expression of RhoB was associated with favorable outcome in bladder cancer.…”
Section: Discussionmentioning
confidence: 53%
“…120,121 The GTP-binding domain of RhoBTBs is expected not to hydrolyse GTP, because they do not have key amino acids required for GTP hydrolysis, including a glycine equivalent to G12 and a glutamine equivalent to Q61 in Ras. 121,122 It has been reported that the GTP-binding domain of RhoBTB2 binds to GTP in vitro, 120 but nothing has been published for RhoBTB1. RhoBTB1 and RhoBTB2 are also bigger than classical GTPases due to the presence of extra domains including 2 broad-complex, tramtrack, bric a brac (BTB) domains, which are conserved proteinprotein interaction domains.…”
mentioning
confidence: 99%
“…The decrease affected to 80% of kidney and to 58% of breast cancer samples. The expression changes correlated with those of CUL3 in the same samples (Berthold et al, 2008) …”
Section: Various Cancers Including Breast Kidney and Stomachmentioning
confidence: 87%
“…RhoBTB1 binds to cullin3 and by analogy to RhoBTB2 and RhoBTB3 may constitute ubiquitin ligase complexes. RhoBTB proteins appear to exist in an inactive state through an intramolecular interaction of the BTB domain region with the GTPase domain (Berthold et al, 2008). This model has been refined recently for RhoBTB2 to show that the HSP90AA1 (Hsp90) chaperone machinery unlocks RhoBTB, enabling GTP binding and interaction with Cullin 3 and the COPS8 (COP9) signalosome.…”
Section: Functionmentioning
confidence: 99%
See 1 more Smart Citation